Esophageal stenosis: A case of delayed dysphagia in an infant from northern Tanzania. (April 2022) - Lodhia, Jay; Chugulu, Samwel; Tendai, Joylene; Philemon, Rune
Abstract: Introduction and importance: Congenital stenosis of the esophagus is often overlooked in children with feeding difficulties leading to delayed diagnosis and treatment. This can have detrimental effects on the child's growth and general health, ranging from malnutrition to life-threatening complications such as aspiration pneumonia. Case presentation: We present a case diagnosed at the age of 3 years when the child already had developed moderate malnutrition and offer the diagnostic and surgical findings in the hope of helping others suspect and clench the diagnosis early. Clinical discussion: With an incidence of up to 1 in 25, 000, congenital stenosis of the esophagus is definitely a congenital malformation worth knowing about, particularly since misdiagnosis often leads to delayed intervention as was in our case. History of feeding difficulty and failure to thrive are often the triggers to seeking medical attention. The confirmation can be easily made with contrast imaging opening up the possibility for surgical and non-surgical management. Conclusion: With a high index of suspicion, diagnosis can be made relatively easily, allowing for early intervention, which can prove to be lifesaving. Highlights: History of feeding difficulty and failure to thrive should raise suspicion. Contrast radiology and endoscopy can easily confirm the diagnosis. Treatment can be surgical or non-surgical depending on size, location and number.